Industrial Training Report: MZN Associates / Mohammad Baharuddin Mohd Yusoff - Mohd Yusoff, Mohammad Baharuddin
My six-month industrial training at MZN Associates was summarized in this report. My industrial training began on October 2, 2022, and will end on March 16, 2023 Encik Mohammad Sufian Bin Mohamed, my supervisor, and Cik Khairun Adani Binti Roslan, a MZN Associates’s officer who gave and shared a lot of information with me, were the person who supported and teach me the most during my internship. I am assigned to four departments in this office which is the Accounting Department, the Auditing Department, the Taxation Department, and the Company Secretary Department. According to the step, by doing the client company account I will go through each department step by step. The goal of this is to gain more knowledge and experience about how was this company operate on doing their service to their client. Furthermore, because of unavailability of the data this report discusses other company which in the same sector as the MZN Associates which is the selected company is Institute of Internal Auditors Malaysia (IIAM). This report discusses IIAM's company's industry analysis in Ten consecutive years. This industry analysis seeks to assess the company's performance in several areas, including profitability ratio, leverage ratio, liquidity ratio, and efficiency ratio, to determine whether it is performing well or poorly. Other than that, it also discusses how to solve the company's problems to improve their performance